Desenvolvimento de tecnologia alternativa para tratamento de efluentes de oficinas mecânicas utilizando eletrocoagulação - Arcego, Cláudio Vinicius (2017)
The Technologies used for treatment of automotive centers, gas stations and car wash stations wastewaters, available in the market have a number of operational limitations. This background, combined with the vehicle fleet increases, requires new technologies for this aim. In this context the mean goal of this work is develop an alternative technology for automotive centers and car wash stations wastewaters treatment. The methodology included: 1) a characterization of the effluent generation sources; 2) qualitative and quantitative characterization of the studied effluent; 3) technological prospecting; 4) the technology proposition; 5) the design and construction of the prototype; 6) experimental planning and performance of operational tests in laboratory conditions; 7) a proposal and systematization of the new technology; And 8) intellectual protection. It should be noted that the main parameters evaluated in this work were the apparent color, turbidity, pH and COD. The technology resulting from this work, for a condition with a higher effluent concentration (C0 = 2.5 mg.mL-1), with pH = 7 and current density (σ) of 3.42 mA.cm- ² presented higher efficiency in the removal of apparent color 99.71%) and turbidity (99.75%). The best performance in reducing the COD (93.5% removal) occurred under the conditions of test 12 (C0 = 1.5 mg.mL-1, σ = 3.42 mA / cm², pH = 10). The pH of the effluents was studied in the range of 4 to 10 and at this condition, it was observed a directly proportional influence between pH and the removal efficiency. After the results systematization and previous inventive activity evaluation, the technology for wastewater treatment must be object of intellectual protection in the National Institute of Industrial Property (INPI). The innovation is classified like Utility Model, since it is a creation of form, structure and disposition, involving an inventive act that resulted in functional improvement.